2001
DOI: 10.1002/ajmg.1549
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for linkage disequilibrium between the alpha 7‐nicotinic receptor gene (CHRNA7) locus and schizophrenia in Azorean families*

Abstract: Recent studies have suggested that the alpha 7-nicotinic receptor gene (CHRNA7) may play a role in the pathogenesis of schizophrenia. The alpha 7-nicotinic receptor gene (CHRNA7) is involved in P50 auditory sensory gating deficits, and the genomic locus for this gene lies in the chromosome 15q13-14 regions. The human gene is partially duplicated (exons 5-10) with four novel upstream exons. The marker D15S1360 has been shown to be significantly linked with the phenotype of abnormal P50 suppression in schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…0.001) was for marker D15S1360, which is physically close to the ·-7 nicotinic acetylcholine receptor (nAChR) subunit gene (CHRNA7). Additional studies using 15q14 markers have implicated CHRNA7 in schizophrenia using linkage [Coon et al, 1994;Riley et al, 1997;Kaufmann et al, 1998;Leonard et al, 1998;Gejman et al, 2001;Liu et al, 2001;Tsuang et al, 2001] and linkage disequilibrium methods [Riley et al, 2000;Stassen et al, 2000;Freedman et al, 2001;Xu et al, 2001]. In contrast, several studies have not confirmed these results [Moises et al, 1995;Pulver et al, 1995;Faraone et al, 1998;Levinson et al, 1998;Neves-Pereira et al, 1998;Curtis et al, 1999;Hovatta et al, 1999;Ekelund et al, 2000;Gurling et al, 2001].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…0.001) was for marker D15S1360, which is physically close to the ·-7 nicotinic acetylcholine receptor (nAChR) subunit gene (CHRNA7). Additional studies using 15q14 markers have implicated CHRNA7 in schizophrenia using linkage [Coon et al, 1994;Riley et al, 1997;Kaufmann et al, 1998;Leonard et al, 1998;Gejman et al, 2001;Liu et al, 2001;Tsuang et al, 2001] and linkage disequilibrium methods [Riley et al, 2000;Stassen et al, 2000;Freedman et al, 2001;Xu et al, 2001]. In contrast, several studies have not confirmed these results [Moises et al, 1995;Pulver et al, 1995;Faraone et al, 1998;Levinson et al, 1998;Neves-Pereira et al, 1998;Curtis et al, 1999;Hovatta et al, 1999;Ekelund et al, 2000;Gurling et al, 2001].…”
Section: Introductionmentioning
confidence: 58%
“…The individual gene analysis further targets specific genes that may have particular involvement, those being CHRNA2, CHRNB2, and possibly CHRNA7 and CHRNA1. Although more research is necessary, the results for CHRNA7 are compelling because this gene has been implicated in schizophrenia and sensory gating deficits by several prior studies [Coon et al, 1994;Freedman et al, 1997Freedman et al, , 2001Riley et al, 1997Riley et al, , 2000Leonard et al, 1998;Stassen et al, 2000;Gejman et al, 2001;Liu et al, 2001;Tsuang et al, 2001;Xu et al, 2001]. Both the complex and individual analyses helps to further prioritize genes for case control studies relating to smoking in schizophrenics.…”
Section: Results Of Hypothesis Testingmentioning
confidence: 96%
“…Maximal linkage to the P50 deficit was found at chromosome 15q14 at a polymorphic marker < 120 kb from the α7 gene with a lod score of 5.3, Θ = 0.0 [39]. Linkage of this region to schizophrenia was further replicated in families from the NIMH Schizophrenia Genetics Initiative [40] and in other studies [41,42,43,44], but there have also been some negative studies in this region [45,46]. Multiple single nucleotide polymorphisms (SNP)have been identified in the 15q14 gene promoter region that are more frequently present in people with schizophrenia and their family members than normal controls [47,48].…”
mentioning
confidence: 77%
“…The locus of the α7 subunit, 15q14, has also been linked to the P50 deficit in schizophrenia with a LOD score of 5.3 . Linkage of this site to schizophrenia has been replicated in multiple studies (Freedman et al, 2001a;Freedman et al, 2001b;Leonard et al, 1998;Xu et al, 2001;Liu et al, 2001;Tsuang et al, 2001;Kaufmann et al, 1998;Stober et al, 2000;Riley et al, 2000). A linkage of smoking in schizophrenia to a dinucleotide repeat in intron 2 of the α7 gene, CHRNA7, was recently reported (De Luca et al, 2004), further supporting a role for the α7* receptor in smoking in schizophrenia.…”
Section: Nicotinic Receptors Are Genetically Linked To Smoking and Scmentioning
confidence: 85%